The Role of Legal Aid Post (Pos Bantuan Hukum) in Serving Uncapable Communities in the Bandung Religious Court - Maulida Zahra Kamila; Nurohman Nurohman; Usep Saepullah (Khazanah Hukum, 2022)
Legal Aid Post (Posbakum) as the role of one's gateway to access justice is intended for those who are economically incapable, it is necessary to know the procedures and mechanisms of legal aid services and the extent to which these roles are deemed effective or not by the beneficiaries. This study focuses on the implementation of legal aid for economically disadvantaged communities in Legal Aid Post (Posbakum) Court using descriptive analysis research methods, the type of data used is empirical juridical,data sources are obtained from primary data and secondary data which are then analyzed qualitatively. The results of the study (1) recipients of legal assistance brought a Certificate of Incapacity (Surat Keterangan Tidak Mampu (SKTM)) from the local village and were brought to the consultation desk to fill out a form that contained in a nutshell the identity of the applicant and a brief description of the subject matter of the case, then legal advice was given by a lawyer or legal aid post (Posbakum) officer. available, if the requirements and forms have been filled in completely, then the typing will be given to assist in making legal documents. (2) The factors that become the benchmark for its effectiveness have not been fully achieved, so it can be said that the legal aid post (posbakum) at Bandung Religious Court has not been effective.